Energy Use of Mediterranean Forest Biomass in Sustainable Public Heating Systems and its Effects on Climate Change – Case of Study - Juan José Mayans; José A. Torrent-Bravo; Leticia Lopéz (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
The municipality of Serra, Valencia, located in the Spanish Mediterranean east coast, covers an area of 5,730 hectares, with 95% of this territory lying within the Sierra Calderona Natural Park and 85% being forest. The main axis of the municipality’s economy has been the construction, reducing the primary sector, resulting in uncontrolled growth of forest and deterioration of the landscape. All this has raised forest fire risk to dangerous levels threatening the natural heritage of Serra and the future of the Serra Calderona Natural Park. The study shows how an adequate model of forest biomass management, through energetic use in sustainable public heating systems, can have positive direct effects in the fight against climate change, considering both economics aspects and environmental effects, and its capacity to contribute to the socioeconomic development of agro forestry regions, fixing its habitants and offering a rural development based on the rational use of their natural resources